FINANCIAL PERFORMANCE ANALYSIS USING ECONOMIC VALUE ADDED, FINANCIAL VALUE ADDED, AND RETURN ON ASSET IN PT. BUANA - Widya Widya; Sunarji Harahap; Elidawati Elidawati; Thomas Sumarsan Goh (Magister Akuntansi, Universitas Atma Jaya Makassar, 2022)
The company has goal of making profit so the company's performance increases well. The concept of measuring financial performance is done by making financial analysis such as measuring company finances with financial ratio analysis. Ratio analysis that can be used by companies is Economic Value Added (EVA), Financial Value Added (FVA), or Return On Assets (ROA). This research technique is a comparative descriptive analysis technique. Primary data were collected and obtained through observational interviews, documentation studies and literature studies, secondary data obtained from literature related to the research topic. Financial reports as the object of research. The results show the analysis of PT.BUANA's financial performance with EVA measurement has a positive increase from 2019 to 2020. Financial performance with EVA has a positive increase which can prove the company operates consistently. In profit, analysis of PT.BUANA's financial performance with the measurement of FVA experienced a negative decline from 2019 to 2020. A negative decline can prove the level of net income generated by the company cannot cover investment in assets in the company. Analysis of PT.BUANA's financial performance with ROA decreased in percentage from 2019 to 2020. This proves the company's ability to use capital and generate profits has decreased.